n + 9n - 8 - 5 = 2n + 3 Solve for n in the equation n + 9n - 8 - 5 = 2n + 3 Step 1: Group the n terms on the left hand side: (1 + 9)n = 10n Step 2: Group the constant terms on the left hand side: -8 - 5 = -13 Step 3: Form modified equation 10n - 13 = 2n + 3 Step 4: Group variables: We need to group our variables 10n and 2n. To do that, we subtract 2n from both sides 10n - 13 - 2n = 2n + 3 - 2n Step 5: Cancel 2n on the right side: 8n - 13 = 3 Step 6: Group constants: We need to group our constants -13 and 3. To do that, we add 13 to both sides 8n - 13 + 13 = 3 + 13 Step 7: Cancel 13 on the left side: 8n = 16 Step 8: Divide each side of the equation by 8 8n/8 = 16/8 n = 2